Simultaneous mapping of water shift and B1(WASABI)—Application to field‐Inhomogeneity correction of CEST MRI data. Issue 2 (9th February 2016) - Schuenke, Patrick; Windschuh, Johannes; Roeloffs, Volkert; Ladd, Mark E.; Bachert, Peter; Zaiss, Moritz
Abstract : Purpose: Together with the development of MRI contrasts that are inherently small in their magnitude, increased magnetic field accuracy is also required. Hence, mapping of the static magnetic field (B0 ) and the excitation field (B1 ) is not only important to feedback shim algorithms, but also for postprocess contrast‐correction procedures. Methods: A novel field‐inhomogeneity mapping method is presented that allows simultaneous mapping of the water shift and B1 (WASABI) using an off‐resonant rectangular preparation pulse. The induced Rabi oscillations lead to a sinc‐like spectrum in the frequency‐offset dimension and allow for determination of B0 by its symmetry axis and of B1 by its oscillation frequency. Results: Stability of the WASABI method with regard to the influences of T1, T2, magnetization transfer, and repetition time was investigated and its convergence interval was verified. B0 and B1 maps obtained simultaneously by means of WASABI in the human brain at 3 T and 7 T can compete well with maps obtained by standard methods. Finally, the method was applied successfully for B0 and B1 correction of chemical exchange saturation transfer MRI (CEST‐MRI) data of the human brain. Conclusion: The proposed WASABI method yields a novel simultaneous B0 and B1 mapping within 1 min that is robust and easy to implement. Magn Reson Med 77:571–580, 2017. © 2016 International Society for Magnetic Resonance in Medicine